A Meta-Analysis of Word Walls' Effectiveness in Improving English Vocabulary Among Junior High School Students. - Panjaitan, Nelson Balisar (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Language plays a crucial role in interpersonal communication, especially in social situations. To communicate effectively, learners need to expand their vocabulary, as vocabulary is the foundation for the four language skills of listening, speaking, reading, and writing. Teaching English as a foreign language can be challenging, especially when it comes to teaching vocabulary, and thus, the teacher needs to find ways to make the learning process more engaging. This study is a meta-analysis that utilizes a literature review to examine the effectiveness of using the Word Wall in enhancing students' English vocabulary. The sample consists of English foreign language learners who used the Word Wall, predominantly from Junior High School levels. The researcher utilized effect size calculation, based on various journal articles and research studies, to determine the effectiveness of the Word Wall strategy. The results of this study, derived from the discussion and conclusion, suggest that the use of the Word Wall has a significant effect in improving English vocabulary, particularly among Junior High School students. Effect sizes, calculated from multiple studies across different regions such as Bandar Lampung, Purworejo, Jakarta, Bandung, Tarakan, and Jakarta, indicate substantial improvements in vocabulary outcomes. Specifically, the Word Wall strategy demonstrated effect sizes of 1.183 and 1.18 at Junior High School and High School levels respectively, with an overall effect size of 3.0 across various regions in Indonesia.